Analisis Analisis Faktor-Faktor yang Mempengaruhi Pemanfaatan Teknologi Aplikasi Telenursing N-SMSIn pada Asuhan Pasien Tuberkulosis dalam Mencegah Terjadinya Tuberkulosis dan Multidrug-Resistant Tuberculosis - Julhana, Julhana; Rahmad, Indra; Ahmad, Ahmad; Arismansyah, Arismansyah (Poltekkes Kemenkes Mataram, 2025)
Tuberculosis is a chronic infectious disease that is caused by Mycobacterium Tuberculosis and mostly it attacks person in productive age. Moreover, it is still a global health problem including in Indonesia. Many factors influence pulmonary tuberculosis disease including environmental factors and behavioral factors. This research aimed to observe the correlation of age, gender, TB contact investigation, history of diabetes mellitus (DM), history of smoking, housing density through risk factor of tuberculosis in Bima District, public health center of Woha in 2024. This research utilized analytical quantitative method with case-control study design. Meanwhile, sampling technique used was purposive sampling. Population of this research were TB patients in Bima District, Public Health Center of Woha in 2024 with 138 people (69 cases + 69 controls) for the sample. This research utilized Chi Square and Logistic Regression Test. Results of this research showed that a significance value (p-value) of age was 0.002 (CI: 2.946–13.179), p-value of gender was 0.000 (CI: 2.251–10.971), p-value of TB contact investigation was 0.000 (CI: 1.683–7.310), p-value of smoking history was 0.004 (CI: 1.402–5.702). Nonetheless, this research concluded that there were significant corrrelations of age, gender, TB contact investigation, smoking history through risk factors of the occurrence of tuberculosis. It is suggested for TB patients to always do continuous medication for 6 months without stopping and for those who do not suffer from TB to always maintain their health such as healthy lifestyle, eating nutritious food, and exercising regularly.